PENGARUH PENGHINDARAN PAJAK, TATA KELOLA DAN KARAKTERISTIK PERUSAHAAN TERHADAP BIAYA HUTANG - Dewi Kusuma Wardani; Hetina Dwi Sari Wardani (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
The aim of this study was to examine the effect of Tax Avoidance, Independent Commissioners, Managerial Ownership, Institutional Ownership, Audit Committee, and Size Company on cost of debt the period 2012-2016. The population in this study was industrial sectors and industrial sectors consumpted goods that listed in Indonesia Stock Exchange (BEI) during 2012-2016. The research samples was determined by using purposive sampling technique, with predetermined criteria, so that obtained 7 industrial sectors and industrial sectors consumpted goods manufacturing companies that qualify as the samples. The data that used in this study was obtained from secondary source. This study used multiple linear regression method as an analysis technique. The result of this research shows that the kepemilikan manajerial have significant positive influence to the cost of debt. Tax avoidance, komisaris independen, kepemilikan institusional, komite audit, and ukuran perusahaan do not have significant influence to the cost of debt. Keywords: Audit committee, cost of debt, independent commissioners, institutional ownership, managerial ownership, firm size, and tax avoidance.